Il mistero dell’Incarnazione nelle "Enarrationes in Psalmos" di Sant’Agostino - Turzyński, Piotr (Vox Patrum, 2024)
The article presents the importance of the issue of the Incarnation in the commentary of St. Augustine to the Psalms. According to the Bishop of Hippo, the Mystery of the Incarnation is one of the key moments of salvation history. Augustine, in the writings of ancient philosophers, did not find a way in which man could achieve the divine world he longs for. However, Christianity showed him the path of humility (via humilitatis) in the Incarnation. In Christ, God assumes the human condition and, without losing any of his divinity, introduces man to the divine world of eternity. Augustine is convinced that the humility of the Son of God in the mystery of the Incarnation makes God’s humility the core of the Christian faith. And the category of humility itself has not only a moral but also a philosophical dimension. By virtue of the Incarnation, Christ becomes a representative of people and a priest who offers himself as an offering to God the Father. And all of His saving work constitutes unity and has its foundation, weight and meaning precisely in the mystery of the Incarnation. Augustine explains the Incarnation in a biblical and figurative way. For him, Christ as God is the Homeland from which man came and to which he is heading, and as a man, he is the Path along which one must follow to reach the goal. Thanks to the Incarnation, human changing time acquires a purposeful character and moves towards its fulfillment in eternity. Augustine explains the Incarnation in a biblical and figurative way. For him, Christ as God is the Homeland from which man came and to which he is heading, and as a man he is the Path along which one must follow to reach the goal. Thanks to the Incarnation, human changing time acquires a purposeful character and moves towards its fulfillment in eternity.